The Potential of Structurally Insulated Panels (SIPs) to Supply Net Zero Carbon Housing - Stephen Finnegan; Robert Edwards; Bushra Al-Derbi; Iona Campbell; Matt Fulton (Buildings, 2022)
Governments throughout the EU and the UK face a persistent challenge of satisfying the continual growth in demand for housing and create zero carbon buildings. This paper presents a novel conceptual framework and empirical results to evaluate the potential for Structurally Insulated Panels (SIPs) to address this challenge. Firstly, we present a comprehensive analysis of the energy performance of a SIPs building in the UK to evaluate the potential for such technologies to satisfy the energy and carbon objectives. Using our unique data set we show that SIPs can exceed the necessary energy efficiency standards and reach Net Zero Carbon. Secondly, we introduce game theory as a novel conceptual framework to understand the incentives of the manufacturers of SIPs and UK/EU authorities. This enables us to identify potential sources of incentive conflict, which inhibit the diffusion of such technologies. We demonstrate that it benefits both parties to engage in medium investment, but the inferior under investment scenario can emerge if the UK/EU does not provide leadership and commitment to SIPs technologies. Regardless of the market design in terms of the timing of decisions, the maximum level of support by both the UK/EU and the SIPs manufacturers cannot be achieved.